Evaluation of groundwater potential for irrigation at the Seberang Perak Aquifer, Malaysia - Jusoh, Mohd Fauzie (2013)
The pumping well performance and aquifer performance in a quaternary sediment of Gula Formation at Seberang Perak Integrated Agricultural Development Area (Seberang Perak IADA) has been investigated quantitatively. The study was conducted in the years of 2009 and 2010 at a selected rice cultivation area. Aquifer performance test was carried out by conducting 24 hours constant discharge pumping test in a shallow alluvial aquifer. The time drawdown data were collected at three different wells. The pumping well performance was evaluated by using continuous step-drawdown pumping test. Time-drawdown data was analyzed by using AquiferTest Pro software version 4.2. The aquifer test enabled the values of hydraulic characteristics of the aquifer material such as transmissivity, hydraulic conductivity, and specific yield to be determined. Well performance was interpreted through well loss coefficient and specific capacity. The predictive analysis of drawdown through multiple pumping well was based on the results of aquifer performance. The type of the aquifer up to about 10 m depth from ground surface at the research area is unconfined aquifer. The Neuman model and Boulton model have been used to evaluate the hydraulic characteristic of the aquifer. The transmissivity value from observation wells varied from 581 to 940 m2day-1 with the average transmissivity of 761 m2day-1. This indicates that the aquifer was categorized as having high groundwater potential. The hydraulic conductivity values obtained from observation well 1 and observation well 2 range from 58.1 mday-1 to 94.0 mday-1. This implies that the aquifer materials are developed from coarse grain sand. The specific yield from observation well 1 and observation well 2 are found to be 0.0041 and 0.0135 respectively. The results of aquifer hydraulic characteristic are in agreement with the recovery test analysis. In term of well performance, the average specific capacity of the pumping well is found to be 6.1223 m2hr-1. Specific capacity of the tested well is classified as having moderate potential. The average well efficiency of the tested tube well is found to be 92%. This showed that the well has been well designed and the screen was installed at the suitable location in the aquifer. The coefficient of aquifer loss and well loss are found to be 0.1513 hrm-2 and 0.002 hr2m-5 respectively. In each step, the drawdown inside the pumping well is influenced more by the aquifer loss compared to the well loss. The potential yield of the pumping well is calculated as 450 m3day-1. Based on the crop water requirement and groundwater irrigation on the field, it is estimated that 4 hectares of paddy plot requires 260 m3day-1. However, the pilot project on groundwater irrigation for rice cultivation on the study site use less than the amount of water calculated from crop water requirement. The result of 24 hours constant discharge pumping test shows that the drawdown at the pumping well is 2.2 m with the total abstraction of 240 m3day-1. Two pumping wells are required to irrigate 4 hectares of paddy plot. The effect of drawdown on multiple pumping well can be predicted through the result of pumping test directly which can save time and minimize the research cost.